Personality Analysis through Handwriting Detection Using Android Based Mobile Device - Wijaya, Waskitha; Tolle, Herman; Utaminingrum3, Fitri (Faculty of Computer Science (FILKOM) Brawijaya University, 2017)
Graphology is one of the psychology disciplines which aims to study the personality traits of individuals through interpretation of handwriting. We can get information of one’s personality through graphology. In addition, by using android based mobile device, graphology analysis could show one’s personality faster. This study was conducted by taking 42 samples of handwriting from different backgrounds. The feature used in this study was handwriting margin. Besides, Support Vector Machine method was employed to classify the result feature from extraction process. The result of this study showed the accurate average of the application reached 82.738%.